Computational Modelling of Accident Conditions in Nuclear Reactors with System Codes and 3D Components Using TRACE5 (LACCEI, 2024)
Computational mechanics is a discipline of high relevance in the nuclear power plants accident assessments. System codes are the most used tools in it, because they can be used to simulate the whole plant and calculate long transients. This is possible because they use zero/one dimensional (0/1-D) component models that permit a reduction in computational costs with adequate macroscopic results. Nonetheless, new reactor designs and the need of reducing uncertainties require a higher detail level. Because of this, some system codes now include tridimensional (3D) components to enhance the geometric nodalization of the nuclear reactor. This is the case of TRACE5 (TRACE/RELAP Advanced Computational Engine), which includes tridimensional components representing a reactor pressure vessel. During the last years, scientists and engineers that work with system codes have performed many tests to validate these components using experimental facilities. This work is a detailed study of the TRACE5 system code, which also includes a sensitivity analysis, in the ROCOM experimental facility. This installation was developed for the analysis of inherent 3D phenomena within a nuclear reactor. On this work the mixture of water flows of different temperatures is studied, and the sensibility of the results respect to the nodalization and the numerical schemes is analysed. The results show good agreement with the experimental values and can be used to define modelling good practices.